2017
DOI: 10.31276/vjste.59(3).71
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of landfill leachate in Nam Son, Hanoi using 3D electrical imaging and self-potential data

Abstract: The main objective of this study was to assess the environmental impact of the Nam Son Landfill on the subsurface geological structure studied using 3D electrical imaging and self-potential investigations. The map of the equipotential was based on self-potential data and was indicative of concentrations of redox-active components, and the map of the electrical conductivity provided information about the mineralization of the groundwater. The electrical conductivity of the subsurface was obtained from 3D-electr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…Amomum maximum is a widely distributed plant of the tropical terrain, which has traditional therapeutic potential and culinary values (Nguyen 2000). An investigation has shown that the extract of A. maximum acts as anthelmintic against the cestode, Raillietina echinobothrida (Chetia et al 2014).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Amomum maximum is a widely distributed plant of the tropical terrain, which has traditional therapeutic potential and culinary values (Nguyen 2000). An investigation has shown that the extract of A. maximum acts as anthelmintic against the cestode, Raillietina echinobothrida (Chetia et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…No record of the composition of its essential oil could be found in the literature. Furthermore, Amomum microcarpum is a plant that can grow up to 2.5 m tall (Nguyen 2000). It has been traditionally used for the treatment of fever and postpartum bath (Lamxay et al 2011;Boer et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…The genus Arisaema Mart. includes about 200 species mainly distributed across Eastern Asia from both temperate and tropical regions as far south as Indonesia and west into the Himalayas with some species occurring in the Arabian Gulf, East Africa and North America (Mayo et al 1997;Govaerts et al 2002;Gusman and Gusman 2006;Boyce et al 2012;Nguyen 2017). Following Gusman & Gusman (2006), the genus Arisaema is divided into 14 sections: Anomala, Arisaema, Attenuata, Clavata, Decipientia Flagellarisaema, Frenchetiana, Lobata, Nepenthoidea, Pedatisecta, Sinarisaema, Tenuipistillata and Tortuosa. The species described here belongs to sect.…”
Section: Introductionmentioning
confidence: 99%
“…Sinarisaema contains 29 species of which three can be found in Vietnam. Currently a total of 26 species of Arisaema belonging to seven sections are now recorded in Vietnam; these are sections: Anomala, Attenuata, Decipientia, Franchetiana, Nepenthoidea, Odorara and Sinarisaema, (Nguyen 1998(Nguyen , 2000(Nguyen , 2002(Nguyen , 2005a(Nguyen , 2005b(Nguyen , 2007(Nguyen , 2017Pham-Hoàng 2000;Nguyen & Boyce 2005;Gusman and Gusman 2006;Nguyen & Vu, 2009;Li et al 2010;Boyce et al 2012;Bruggemen et al 2013;Luu et al 2013Luu et al , 2014Luu et al , 2020Luu et al , 2022Nguyen et al 2014;Hoang et al 2015;Ohi-Tomi et al 2016;Van et al 2016aVan et al , 2016bVan et al , 2017Van 2017;Le et al 2020) with a single representative from sect. Nepenthoidea only very recently added to those recorded in Vietnam with the discovery of a new species in 2022 from Pu Ta Leng Mountain, in Tam Duong District, Lai Chau Province (Luu et al 2022).…”
Section: Introductionmentioning
confidence: 99%